Quamvis aliter alibi scripserim: Motivo ed esiti di una ritrattazione tommasiana circa il sapere umano di Gesù - Duchi, Simone (Rassegna di teologia, 2022)
Challenging the agreement of contemporary theologians, Thomas Aquinas changes his opinion with respect to the quaestio de scientia Christi discussed in his youth. The study probes the reasons for the rethinking and sheds light on the theme to which it pertains. The considered area is strategic: theological truth depends on the knowledge of the Nazarene, because that one is a christological truth. Consequently it doesn't simply matter what Christ knew in the days of his earthly life, but which is the theological significance of this knowledge.